2021
DOI: 10.1101/2021.10.20.463454
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evolutionary trade-offs between heat and cold tolerance limit responses to fluctuating climates

Abstract: The evolutionary potential of species to cope with short-term temperature fluctuations during reproduction is critical to predicting responses to future climate change. Despite this, vertebrate research has focused on reproduction under high or low temperatures in relatively stable temperate climates. Here, we characterize the genetic basis of reproductive thermal tolerance to temperature fluctuations in the ostrich that lives in tropical and sub-tropical Africa. Both heat and cold tolerance are under selectio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 62 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…Thus, we found no evidence for a trade-off between heat-and cold-acclimation at the level of thermoregulation. While such a trade-off might be perceived as intuitive and sometimes occurs at the organismal level (Shou et al, 2022), it need not be expected on regulatory grounds where thermogenesis and thermolysis are not physiologically linked. Nonetheless, we found that coldacclimated birds had higher baseline (i.e., non-heat-induced) EWL than control birds (Fig.…”
Section: Journal Of Experimental Biology • Accepted Manuscriptmentioning
confidence: 99%
“…Thus, we found no evidence for a trade-off between heat-and cold-acclimation at the level of thermoregulation. While such a trade-off might be perceived as intuitive and sometimes occurs at the organismal level (Shou et al, 2022), it need not be expected on regulatory grounds where thermogenesis and thermolysis are not physiologically linked. Nonetheless, we found that coldacclimated birds had higher baseline (i.e., non-heat-induced) EWL than control birds (Fig.…”
Section: Journal Of Experimental Biology • Accepted Manuscriptmentioning
confidence: 99%
“…Larger bodies have a higher thermal inertia and slower rate of body temperature change compared to small bodies (Bogert, 1949;Angiletta, 2009). Thermal inertia can help maintain body temperatures during cold conditions, but it can also increase physiological stress under sustained heat, jeopardising survival and reproduction (Hurley et al, 2018;Sales et al, 2018;Bourne et al, 2020;Parratt et al, 2021;Schou et al, 2021Schou et al, , 2022.…”
Section: Introductionmentioning
confidence: 99%
“…Estimating additive genetic variance in thermoregulation, and its relationship to fitness, requires measuring these traits across hundreds of individuals of known pedigree. To do this we studied a captive population of ostriches in the Klein Karoo region of South Africa, where a large number of individuals have been reared in a semi-natural environment over 25-years to produce a large nine-generation pedigree (Schou et al, 2021(Schou et al, , 2022. To quantify thermoregulation, we used thermal imaging (infrared camera technology) as this technique allows the surface temperature of hundreds of individuals to be non-invasively measured (Tattersall & Cadena, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations